Teaching personal and social responsibility: An analysis of TPSR-based behaviors in physical education - Rama Adha Septiana; Tite Juliantine (Physical Education and Sports: Studies and Research, 2025)
Background: The rapid growth of online gaming among students has raised concerns regarding behavioral regulation, responsibility, and social interaction in educational contexts. Objectives: This study aims to systematically review empirical research on the Teaching Personal and Social Responsibility (TPSR) model and student behavioral outcomes, and to explore its potential implications for online gaming and digital behavior contexts. Methods: A literature review was conducted using SAGE Journals and Taylor & Francis Online databases, selected due to their strong coverage of peer-reviewed research relevant to physical education and pedagogy. The search covered publications from 2014 to 2024 using the keywords “TPSR” AND “student” AND “behavior” AND (“online game” OR “gaming”). Inclusion criteria were: (1) peer-reviewed international journal articles, (2) empirical or review studies addressing TPSR and student behavior, (3) student populations, and (4) publication within the last ten years. Articles that did not explicitly address TPSR-based behavioral outcomes were excluded. From 43 initial records, 4 articles met the inclusion criteria and were synthesized using narrative synthesis. Results: The included studies primarily focused on TPSR implementation in physical education contexts, emphasizing behavioral responsibility, psychosocial mechanisms, and pedagogical approaches. Of the four studies, two employed quasi-experimental designs, one used survey methods, and one adopted a literature review approach. Overall, the findings indicate that TPSR-based learning is associated with improvements in personal and social responsibility, positive behavior regulation, and supportive learning climates, although direct evidence linking TPSR to online gaming behavior remains limited. Conclusions: The findings suggest that TPSR offers a promising pedagogical framework for fostering responsible behavior and social regulation among students in the digital era.